German validation of three ethics questionnaires: consequentialist scale, ethical standards of judgment questionnaire, and revised ethics position questionnaire - Teichmann, Birgit; Melchior, Florian; Kosteletos, George (PLOS ONE, 2025)
Introduction The Consequentialist Scale (CS) and the Ethical Standards of Judgment Questionnaire (ESJQ) are instruments developed to evaluate the extent of moral reasoning in relation to the two pivotal factors that appear to influence moral decision-making: the degree of harm or benefit produced by the action in question and the consistency of the action with moral norms. In other words, they assess the propensity to utilitarian versus deontological moral reasoning. In contrast, the Ethical Position Questionnaire (EPQ-5) conceptualizes ethical idealism and ethical relativism as meaning-independent, orthogonal dimensions. This study aimed to assess the psychometric properties of German versions of the three mentioned scales in a sample of native German speakers. Methods A convenience sample of 263 participants completed the online survey. Analyses included internal consistency, structural validity, construct validity through the known-groups method, retest-reliability with a subgroup of n = 102, and floor and ceiling effects. This study used the STROBE checklist. Results The CS and EPQ-5 showed strong psychometric properties without any noticeable weaknesses. In contrast, the ESJQ displayed significant shortcomings across all analyses, with low internal consistency and poor results in both item analysis and confirmatory factor analysis. The results indicated that deontology, formalism, and idealism were positively correlated with age, while only idealism correlated significantly with gender, with females scoring higher on the idealism scale. A positive correlation was observed between deontology and formalism with religiosity. With regard to personality, deontology and idealism demonstrated a positive correlation with conscientiousness, whereas utilitarianism exhibited a negative correlation with conscientiousness. A positive correlation between consequentialism and openness was also identified, while a negative correlation between formalism and agreeableness was evident. Conclusion The German versions of the CS and EPQ-5 are reliable and valid instruments for measuring the propensity toward utilitarian and deontological approaches, as well as ethical idealism and relativism. The scales, therefore, serve as invaluable tools for research, training, and professional practice, facilitating comprehension of the aspects of conscious reflection on ethical dilemmas in practice and of responsible action. The ESJQ, however, did not perform well psychometrically in the German translation, as its internal consistency is questionable.
Gesehen am 27.10.2025